Sodelovanje delavcev pri upravljanju v enotirnem sistemu upravljanja - Strojin Štampar, Anja (Delavci in delodajalci, 2018)
The article contains an overview of the key duties and liability of employee representatives on the board of directors and of employee executive directors in a stock company with one-tier governance system, based on the analysis of the relevant Slovenian legislation and jurisprudence. Special duties of board of directors and employee representatives result in the extended liability of board of directors for overall management and business performance of a company. The appropriateness of the employee representation model in the one-tier corporate governance system has also been confirmed by the Slovene Constitutional Court, which has held that the employee participation in the one-tier governance system had been regulated on a comparable but not identical level as employee participation in the two-tier governance system.
Keywords: board of directors; corporate governance; delavski izvršni direktor; delavsko soupravljanje; delniške družbe; director's duties and liability; employee executive director; employee participation; enotirni sistem upravljanja; korporativno upravljanje; one-tier governance system; skrbnost in odgovornost; stock company; upravni odbor